Penerapan Teori Perkembangan Sosial Dan Kepribadian Erikson Dalam Pendidikan: Pendekatan Psikososial Untuk Optimalisasi Pembelajaran - Rizki, Najrul jimatul (Epistemic: Jurnal Ilmiah Pendidikan, 2024)
This study aims to explore the application of Erik Erikson’s theory of social and personality development within the educational context, which is highly relevant in supporting students’ holistic development. The research background is based on the importance of understanding the psychosocial development stages that individuals face throughout their lives, particularly within educational settings. The main objective of this study is to analyze how Erikson’s theory can be applied by educators to support students’ social, emotional, and intellectual growth. The research methodology employs a descriptive qualitative approach through literature reviews and secondary data analysis from various scientific sources. This study is designed to deeply investigate key aspects of Erikson’s theory, such as identity, collaboration, and conflict resolution, as well as how cultural values can influence individual development. The findings indicate that the application of Erikson’s theory in education can help educators create learning environments that foster students’ identity development, encourage collaboration, and facilitate conflict resolution. The implications of this research are significant for educators in designing a more inclusive curriculum that is responsive to students’ psychosocial developmental stages while respecting their cultural diversity and social context.